1986
DOI: 10.1139/e86-105
|View full text |Cite
|
Sign up to set email alerts
|

Imbricated terranes of the Cariboo gold belt with correlations and implications for tectonics in southeastern British Columbia

Abstract: The Cariboo gold belt of east-central British Columbia is divided into four fault-bounded sequences of distinct stratigraphy. They are, from east to west, the Cariboo (continental-shelf sediments), Barkerville (continental-shelf sediments and intercalated volcanics), Slide Mountain (rift-related submarine pillow basalt, chert, and diorite) and Quesnel (island-arc sediments and subaqueous volcanics) terranes. Each is separated from others by thrust faults. Grit, phyllite, limestone, and volcanics of the Barkerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The Paleozoic paleogeography is widely viewed as a passive margin that included a platform and shelf, dominated by carbonate rocks with subordinate clastic rocks that passed laterally westward into an oceanic basin with finer-grained, deeper-water facies (the Cordilleran miogeocline). Elaborating on the concept of episodic (Proterozoic to mid-Paleo zoic) heterogeneous thinning of the western margin of North America (Okulitch, 1984;Struik, 1986), Thompson et al (2006) argued that the outboard (western) side of the Neoproterozoic through early Mesozoic North American margin was defined by a "ribbon" of continental crust called the "Okanagan High" at least 200 km wide and several hundred kilometers long. The Okanagan High would include the Monashee and Selkirk metamorphic sequences and most of the basement of the Quesnel volcanic arc.…”
Section: Regional Paleogeography and Stratigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…The Paleozoic paleogeography is widely viewed as a passive margin that included a platform and shelf, dominated by carbonate rocks with subordinate clastic rocks that passed laterally westward into an oceanic basin with finer-grained, deeper-water facies (the Cordilleran miogeocline). Elaborating on the concept of episodic (Proterozoic to mid-Paleo zoic) heterogeneous thinning of the western margin of North America (Okulitch, 1984;Struik, 1986), Thompson et al (2006) argued that the outboard (western) side of the Neoproterozoic through early Mesozoic North American margin was defined by a "ribbon" of continental crust called the "Okanagan High" at least 200 km wide and several hundred kilometers long. The Okanagan High would include the Monashee and Selkirk metamorphic sequences and most of the basement of the Quesnel volcanic arc.…”
Section: Regional Paleogeography and Stratigraphymentioning
confidence: 99%
“…Antler-age tectonism was inferred from the Late Devonian through mid-Mississippian flooding of the Cordilleran miogeocline by westerly derived clastics, which required a highland to the west. This clastic influx is represented by the coarse clastics of the Guyet Formation at Alberta latitudes in the Cariboo Mountains (Campbell et al, 1973) and by the Earn Group farther north in the Cassiar Mountains and the Yukon (Gordey et al, 1987), with their eastern fine fringe consisting of the Exshaw Formation and Besa River Formation, respectively, which spread far into the interior of the platform from Frasnian to earliest Mississippian time (Campbell et al, 1973;Struik, 1986;Gordey et al, 1991). The western sequences that include coarse sandstone and conglomerate are associated with growth faults and local alkali volcanic rocks of continental-rift geochemistry (Goodfellow et al, 1995).…”
Section: Western Sourcesmentioning
confidence: 99%
“…The Cariboo terrane has been identified as a representative piece of the ancestral North American margin. This portion of the terrane contains carbonate and siliciclastic rocks (Struik, 1986;Ferri and Schiarizza, 2006).…”
Section: Geology Of the Study Areamentioning
confidence: 99%
“…Pre-Mississippian contraction and deformation may have occurred in the Kootenay arc to the west and southwest of the study region in southeastern British Columbia and northeasternmost Washington (e.g., Read and Wheeler 1976;Klepacki and Wheeler 1985;Smith and Gehrels 1992), although the timing and nature of deformation are not well constrained. Middle Paleozoic igneous activity has also been noted to the west and north of the Kootenay arc (e.g., Okulitch 1985), as has evidence of tectonism in central British Columbia (Cariboo orogeny ;White 1959;Struik 1986;Smith et al 1993). Struik (1986) interpreted the Exshaw Formation of the adjacent Rocky Mountains to the east as a distal part of a graben-edge uplift sequence (extensional regime), whereas Smith et al (1993) suggested that the Exshaw facies could be distal foreland deposits.…”
Section: Paleogeography-a Link Between Tectonics and Sedimentation?mentioning
confidence: 99%
“…Middle Paleozoic igneous activity has also been noted to the west and north of the Kootenay arc (e.g., Okulitch 1985), as has evidence of tectonism in central British Columbia (Cariboo orogeny ;White 1959;Struik 1986;Smith et al 1993). Struik (1986) interpreted the Exshaw Formation of the adjacent Rocky Mountains to the east as a distal part of a graben-edge uplift sequence (extensional regime), whereas Smith et al (1993) suggested that the Exshaw facies could be distal foreland deposits. In addition, quantitative subsidence analyses of Paleozoic strata in Alberta (e.g., Bond and Kominz 1991;Prophet Trough of Richards 1989) and the Antler foreland in Idaho and Montana (e.g., Dorobek et al 1991a;Dorobek et al 1991b) (Fig.…”
Section: Paleogeography-a Link Between Tectonics and Sedimentation?mentioning
confidence: 99%